Pengaruh Kinerja Keuangan Terhadap Green Banking Disclosure dengan Mekanisme Kontrol sebagai Variabel Moderasi - Lulu Lugina Kurniawan (Jurnal Ilmiah Wahana Akuntansi, 2021)
This study aims to determine the effect of Financial Performance on Green banking Disclosures, with a control mechanism as a moderating variable. The control mechanisms used in this study are the Board of Commissioners, the Audit Committee and Public Ownership. The method used is content analysis of 21 items of Green Banking Disclosure based on the Green Banking Disclosure Index (GBDI) developed by Bose at al. (2018). Model Moderating Regression Analysis (MRA) using SPSS software. The population in this study were all banks listed on the IDX during 2017-2019 and reported Green Banking Disclosures respectively. The results showed that financial performance directly had a positive effect on Green Banking Disclosure. Of the three elements of the control mechanism, only Public Ownership variables moderate the positive effect of Financial Performance on Green banking Disclosures. Meanwhile, the Board of Commissioners and the Audit Committee failed to moderate the effect of financial performance on Green Banking Disclosures. However, together these three control mechanism variables significantly moderate the positive influence of financial performance on Green Banking Disclosures in banking companies listed on the IDX during the study period.